Knowledge Inspiration and Participation of Student towards School Forest Conservation - Kokfai, Nounchan (วารสารวิชาการมหาวิทยาลัยอีสเทิร์นเอเชีย ฉบับวิทยาศาสตร์และเทคโนโลยี (Online), 2015)
The quasi-experimental research was conducted with 30 high school students of Chiang Yuen School that were collected by purposive sampling technique based on criteria of public mind and commitment to participate throughout research operation. The objectives were to compare the mean scores between pretest and posttest of knowledge of school forest conservation, environmental education, inspiration of environmental conservation, and environmental conservation behavior and to evaluate student participation in training process. Three Dimensional Evaluation (TDE) was employed for determination the participation. One-way ANOVA was used to determine the mean cores difference of three groups. After Participation-Appreciation-Influence-Control (PAIC) finished, the results disclosed that mean scores of posttest of knowledge of school forest conservation, environmental education, inspiration of environmental conservation, environmental conservation behavior and training achievement were higher than pretest with statistical significance (p < 0.01 in all aspects). In present situation demonstrated that mean scores were different with statistical significance (p < 0.01) but in future situation the mean scores were not different with statistical significance (p > 0.05).